2018
DOI: 10.1186/s12885-018-5040-z
|View full text |Cite
|
Sign up to set email alerts
|

Cetuximab for esophageal cancer: an updated meta-analysis of randomized controlled trials

Abstract: BackgroundIncreasing evidence indicates that cetuximab (CET) combined with chemoradiotherapy may be effective for patients with esophageal cancer. However, the recent results are still contradictory and no consensus has yet been reached on this issue. To evaluate the clinical effects and safety of CET, we conducted an updated meta-analysis by retrieving published data up to June 2018.MethodsA comprehensive literature search was performed in several electronic databases, including PubMed, Embase, the Cochrane L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 35 publications
0
24
1
Order By: Relevance
“…Erlotinib and cetuximab demonstrated notable beneficial effects on the DCR in OC, which was consistent with the results of previous studies. 48 57 Most meta-analyses have only reported results for mAb and TKI therapy, without specifying the individual drugs; therefore, it was impossible to verify the effectiveness of each drug.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Erlotinib and cetuximab demonstrated notable beneficial effects on the DCR in OC, which was consistent with the results of previous studies. 48 57 Most meta-analyses have only reported results for mAb and TKI therapy, without specifying the individual drugs; therefore, it was impossible to verify the effectiveness of each drug.…”
Section: Discussionmentioning
confidence: 99%
“…However, cetuximab did not significantly increase the OS, which was consistent with the data from a previous report. 48 It has been suggested that the reduced efficacy of cetuximab in combination with CRT is due to proinflammatory and antitumour proliferative effects of this mAb. 49 Moreover, cetuximab may limit the free radical-induced DNA damage by platinum drugs, 50 which could also explain the non-significant outcomes in this meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Huang's report, for patients with ESCC with high EGFR expression, cetuximab could not only improve survival but also reduce the recurrence and metastatic potential of the tumor. 14 Combining cetuximab with chemotherapy drugs is a novel strategy for esophageal cancer therapy. Yar Saglam et al revealed that the combination of cetuximab and cucurbitacin B can significantly inhibit growth and migration of colorectal cancer cells.…”
Section: Targeting Key Signaling Pathwaysmentioning
confidence: 99%
“…Unfortunately, cetuximab did not produce the same encouraging results for EC. A recent meta-analysis of 10 clinical trials over the past decade concluded that cetuximab (in combination with chemotherapy) did not demonstrate efficacy for improving survival of patients with either local or advanced EC, although it did improve the response rate in the latter [15]. Similarly, panitumumab, another anti-EGFR mAb, failed to improve survival in a phase III trial in which it was combined with chemotherapy [16].…”
Section: Targeted Therapiesmentioning
confidence: 99%